Arbuscular mycorrhizae influence raspberry growth and soil fertility under conventional and organic fertilization - Lu, Qianwen; Bunn, Rebecca; Whitney, Erika; Feng, Yuanyuan; DeVetter, Lisa Wasko; Tao, Haiying (Frontiers in Microbiology, 2023)
Introducing beneficial soil biota such as arbuscular mycorrhizal fungi (AMF) to agricultural systems may improve plant performance and soil fertility. However, whether bioinocula species composition affects plant growth and soil fertility, and whether fertilizer source influences AMF colonization have not been well characterized. The objectives of this research were to: 1) assess if AMF bioinocula of different species compositions improve raspberry (Rubus idaeus L.) performance and characteristics of soil fertility and 2) evaluate the impact of fertilizer source on AMF colonization. Five bioinocula with different AMF species compositions and three fertilizer sources were applied to tissue culture raspberry transplants in a randomized complete block design with eight replicates. Plants were grown in a greenhouse for 14 weeks and plant growth, tissue nutrient concentrations, soil fertility, and AMF root colonization were measured. Shoot K and Zn concentrations as well as soil pH and K concentration increased in the Commercial Mix 1 treatment (Glomus, Gigaspora, and Paraglomus AMF species) compared to the non-inoculated control. RFI (raspberry field bioinoculum; uncharacterized AMF and other microbiota) increased soil organic matter (SOM), estimated nitrogen release (ENR), and soil copper (Cu) concentration compared to the non-inoculated control. Furthermore, plants receiving the Mix 1 or RFI treatments, which include more AMF species, had greater AMF root colonization than the remaining treatments. Plants receiving organic fertilizer had significantly greater AMF colonization than conventionally fertilized plants. Taken together, our data indicate that coupling organic fertilizers and bioinocula that include diverse AMF species may enhance raspberry growth and soil fertility.